Single-cell analysis of skeletal muscle macrophages reveals age-associated functional subpopulations - Krasniewski, Linda K; Chakraborty, Papiya; Cui, Chang-Yi; Mazan-Mamczarz, Krystyna; Dunn, Christopher; Piao, Yulan; Fan, Jinshui; Shi, Changyou; Wallace, Tonya; Nguyen, Cuong; Rathbun, Isabelle A; Munk, Rachel; et al. (eLife, 2022)
Tissue-resident macrophages represent a group of highly responsive innate immune cells that acquire diverse functions by polarizing toward distinct subpopulations. The subpopulations of macrophages that reside in skeletal muscle (SKM) and their changes during aging are poorly characterized. By single-cell transcriptomic analysis with unsupervised clustering, we found 11 distinct macrophage clusters in male mouse SKM with enriched gene expression programs linked to reparative, proinflammatory, phagocytic, proliferative, and senescence-associated functions. Using a complementary classification, membrane markers LYVE1 and MHCII identified four macrophage subgroups: LYVE1−/MHCII hi (M1-like, classically activated), LYVE1+/MHCII lo (M2-like, alternatively activated), and two new subgroups, LYVE1+/MHCII hi and LYVE1−/MHCII lo . Notably, one new subgroup, LYVE1+/MHCII hi , had traits of both M2 and M1 macrophages, while the other new subgroup, LYVE1−/MHCII lo , displayed strong phagocytic capacity. Flow cytometric analysis validated the presence of the four macrophage subgroups in SKM and found that LYVE1− macrophages were more abundant than LYVE1+ macrophages in old SKM. A striking increase in proinflammatory markers ( S100a8 and S100a9 mRNAs) and senescence-related markers ( Gpnmb and Spp1 mRNAs) was evident in macrophage clusters from older mice. In sum, we have identified dynamically polarized SKM macrophages and propose that specific macrophage subpopulations contribute to the proinflammatory and senescent traits of old SKM.